The Effect of Smoking on the Outcome of Matrix-Based Autologous Chondrocyte Implantation: Data from the German Cartilage Registry - Betz, Volker M.; Holzgruber, Martin; Simon, Johanna; Uhlemann, Felix; Niemeyer, Philipp; Müller, Peter E.; Niethammer, Thomas R. (The Journal of Knee Surgery, 2021)
Smoking is known to have various deleterious effects on health. However, it is not clear whether smoking negatively affects the postoperative outcome following matrix-based autologous cartilage implantation (MACI) in the knee. The purpose of this study was to evaluate the effect of smoking on the outcome of MACI in the knee. A total of 281 patients receiving MACI in the knee between 2015 and 2018 were registered in the German Cartilage Database. The cohort was divided into ex-smokers, smokers, and nonsmokers. Data regarding the Knee Injury and Osteoarthritis Outcome Score (KOOS), the numeric rating scale (NRS) for pain, and satisfaction with the outcome were analyzed and compared. Follow-ups were performed at 6, 12, and 24 months after surgery. Of the 281 patients, 225 (80.1%) were nonsmokers, 43 (15.3%) were smokers, and 13 (4.6%) were ex-smokers. The three groups were comparable with respect to age, sex, body mass index (BMI), height, defect size, the need for additional reconstruction of the subchondral bone defect, number of previous knee surgeries, and defect location. However, nonsmokers had a significantly lower weight as compared with smokers. Besides a significantly lower preoperative NRS of nonsmokers as compared with smokers, there were no significant differences between the three groups with respect to KOOS, NRS, and satisfaction at 6, 12, and 24 months of follow-ups. The present study of data retrieved from the German Cartilage Registry suggests that the smoking status does not influence the outcome of MACI in the knee.
Keywords: smoking; autologous cartilage implantation; cartilage repair; knee; German Cartilage Registry